OPTIMALISASI MINAT BELAJAR MURID MELALUI MEDIA POSTER MATA PELAJARAN PENDIDIKAN PANCASILA TEMA HAK DAN KEWAJIBAN KELAS 5 SDN PAKIS V SURABAYA. - Annisa Delvira Putri Wibiyanti; Yudha Popiyanto; Leni Yuliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Optimizing Students' Learning Interest through Poster Media in Pancasila Education Subjects on Rights and Obligations Theme for Grade 5 of SDN Pakis V Surabaya, Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Wijaya Kusuma University Surabaya. Yudha Popiyanto, S.Pd., M.Pd. and Leni Yuliana S.Pd., M.Pd. This study aims to optimize students' learning interest through the use of poster media in Pancasila Education subjects on rights and obligations theme in grade V of SDN Pakis V Surabaya. This study uses a qualitative descriptive approach with a One-Shot Case Study design and involves 8 students as research subjects. Data collection was carried out through observation, interviews, and documentation with instruments in the form of student learning interest observation sheets that include indicators of attention, enthusiasm, activeness, perseverance, and feelings of pleasure during learning using poster media. Data were analyzed descriptively using percentages. The results of the study indicate that the use of posters increased students' interest in learning by an average of 87.38%, which is considered very high. Therefore, posters are an effective way to optimize student interest in Pancasila Education.